PENGARUH MEDIA EDUKASI FLASH CARDS TERHADAP PENGETAHUAN SISWA MENGENAI PENCEGAHAN DM TIPE 2 (Studi di MI Al-Inayah Kota Bandung) - Fiddiya, Ossy Rachmalia; Ruhmawati, Tati (Jurnal Kesehatan Siliwangi, 2024)
Background: The prevalence of diabetes in children has increased 70 times higher. Purpose: To enhance students' knowledge regarding type 2 diabetes prevention at MI Al-Inayah Kota Bandung. Method: The research design employs a mixed-method approach. Quantitative method with quasi-experimental design, with one group pretest-posttest design. The population was taken with a total sampling technique of 46 students in grade 4. Knowledge data were collected using questionnaires and interviews and then analyzed using the Wilcoxon Signed Rank test. Qualitative method with exploratory sequintal design. The population was taken with purposive sampling technique totaling 5 students. Data collection was done using interview techniques. Results: The study results of qualitative produced media regarding the prevention of type 2 DM. Meanwhile the study results of quantitative showed an increase in students' knowledge scores by 41 points. Conclusion: There is an influence of flash cards educational media on improving students' knowledge about type 2 diabetes at MI Al-Inayah Kota Bandung.